Factors influencing mycelial growth of Sclerotium rolfsii - Bhagat, Imdramani (Nepalese Journal of Biosciences, 2013)
Sclerotial blight of tea (Camellia sinensis L.) caused by Sclerotium rolfsii Sacc. is one of the destructive diseases in tea growing areas of the world. In the present investigation, an attempt was made to know the optimum conditions for the mycelial growth of S. rolfsii. Factors influencing mycelial growth of S. rolfsii were studied with special reference to their growth in different media, variable pH and variable sources of carbon (viz., 6 types) as well as organic (viz., 4 types) and inorganic (viz., 4 types) nitrogen sources. Maximum growth of pathogen occurred after 8 days of inoculation at pH 6. Dextrose was the most effective carbon source and yeast extract (organic source) was found most optimum for growth of S. rolfsii. Organic nitrogen sources were found to be better than inorganic nitrogen sources. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7466 Nepalese Journal of Biosciences 1: 26-31 (2011)